Peran Citra Tubuh terhadap pola konsumsi mahasiswa di Merauke - Umakaapa, Muktamar (Journal of Health Education and Literacy, 2024)
Changes in consumption patterns in adolescents are often motivated by body image. This perception leads to an increase in the incidence of obesity and nutritional problems in adolescents. This study aims to analyze the relationship of body image with consumption patterns in students in Merauke. The population is students of the class of 2022 in the physical education health and recreation education program of musamus University as many as 89 people. Sampling technique using simple random sampling with a total of 72 respondents. This study is a quantitative descriptive research with cross sectional design. Data analysis was done univariate and bivariate with Chi Square test. The results of Chi Square test on appearance orientation toward student consumption patterns obtained p value = 0.047 < (0.05) which means there is a meaningful relationship. The results of Chi Square test on anxiety to be fat on student consumption patterns obtained p value = 0.003 < (0.05) which means there is a meaningful relationship. Chi Square test results satisfaction with body parts with consumption patterns in students obtained p value = 0.881 > (0.05) which means there is no relationship. This study concluded that there is a significant relationship between appearance orientation, anxiety to be obese to student consumption patterns. Researchers recommend the campus to conduct socialization activities to students in order to improve their understanding of healthy and proper eating patterns.